2011
DOI: 10.1177/0734242x11423286
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of pharmaceutical waste management at selected hospitals and homes in Ghana

Abstract: The practice of use and disposal of waste from pharmaceuticals compromises the safety of the environment as well as representing a serious health risk, as they may accumulate and stay active for a long time in the aquatic environment. This article therefore presents the outcome of a study on pharmaceutical waste management practices at homes and hospitals in Ghana. The study was conducted at five healthcare institutions randomly selected in Ghana, namely two teaching hospitals (hospital A, hospital B), one reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
43
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 7 publications
6
43
1
Order By: Relevance
“…This was in agreement with results of the Environmental Quality Authority (EQA) survey that was conducted in 2005 in the West Bank and Gaza Strip (EQA, 2005). Similar results were also reported in studies conducted in Egypt (Hussein and Selim, 2008), Portugal (Ferreira and Ribau-Teixeira, 2009), Nigeria (Abah and Ohimain, 2011), and Ghana (Sasu et al, 2011).…”
Section: Impact Of the Educational Program On Practicesupporting
confidence: 87%
“…This was in agreement with results of the Environmental Quality Authority (EQA) survey that was conducted in 2005 in the West Bank and Gaza Strip (EQA, 2005). Similar results were also reported in studies conducted in Egypt (Hussein and Selim, 2008), Portugal (Ferreira and Ribau-Teixeira, 2009), Nigeria (Abah and Ohimain, 2011), and Ghana (Sasu et al, 2011).…”
Section: Impact Of the Educational Program On Practicesupporting
confidence: 87%
“…21 In a study conducted by Sasu s et al, it was found that half of the population surveyed confirmed having unused, leftover, or expired medicines at home, and over 75% population disposed them through the normal waste bins, which end up in the landfills or dump sites. 22 However, in our study 94.7% respondents reported open disposal of the medications.…”
Section: Discussioncontrasting
confidence: 38%
“…It is of interest to note that most of the antibiotics used by the respondents were penicillins which are â-lactamase sensitive with established resistance profile 25,26 . The resistance profile of penicillins generally is poor in the locality where the study was carried out 27,28,29 and as reported in a study conducted in Cape Coast in Ghana 30,31 . It is safe to say that this kind of practice found with the respondents in this study might be a contributory factor to the rising rates of resistance to antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…The act of flushing this class of drugs down the toilet, or throwing it away with refuse may also encourage resistance to these antibiotics of some of the pathogens that may be found in the sewage. Two separate studies have documented that these methods of disposal of antibiotics do not only lead to the development of multidrug resistant strains of pathogens but also can negatively impact on the environment and cause serious health risk 31,32 . In the study by Mispagel & Gary 32 , there was a high number of antibiotic resistant bacteria from pond discharges which was linked to flushing unused antibiotic medications down the toilet by residents.…”
Section: Discussionmentioning
confidence: 99%